Design and Synthesis of 4‐Alkyl‐2‐amino(acetamino)‐6‐aryl‐1, 3‐thiazine Derivatives as Influenza Neuraminidase Inhibitors. Issue 9 (7th August 2013) - Li, Wan; Xia, Lin; Hu, Aixi; Liu, Ailin; Peng, Junmei; Tan, Weiqing
Abstract With a convenient and economical method, two series of 1, 3‐thiazine derivatives 1 and 2 were synthesized, and their neuraminidase (NA) inhibitory activities were evaluated. The pharmacological results showed that most of the compounds have potent NA inhibitory activity. Especially, 1g exhibited the best activity against influenza virus A (H1N1) NA (IC50 = 29.06 µg/mL), and its crystal structure was determined by single‐crystal X‐ray diffraction. The preliminary biological assay indicated that 1, 3‐thiazine could be used as a core structure to design novel influenza NA inhibitors.